Biostatistics : a foundation for analysis in the health sciences. - Daniel, Wayne W., ....- (Hoboken : Wiley, 2005)
A new edition of the bestselling Biostatistics textbook. This classic text takes a more applied and computer-oriented approach to its topical coverage. Like its predecessors, the Eighth Edition stresses intuitive understanding of principles rather than learning by mathematical proof. It provides broad coverage of statistical procedures used in all the health science disciplines. Nearly all the examples and exercises make use of real data from actual research projects and reports from health sciences literature. Where appropriate, Minitab, SPSS and SAS commands and printouts are included as part of the examples and solutions to exercises.
Keywords: Biometrie